Integrating Training Pills and Flipped Classroom Model to Enhance B2-Level Writing Skills in EFL Learners: A Quasi-Experimental Study - Felix Martinez, Jose Maria; Safeer, Nadia; Choudhry, Lubna; H. Alaqad, Mohammed (WISE Pendidikan Indonesia, 2024)
Writing proficiency, especially at the B2 level in English as a Foreign Language (EFL), poses challenges for learners, necessitating mastery of various competencies, including linguistic accuracy and content organization. This study investigates the effectiveness of integrating